Cosmic Emotions; or, Why Is the Universe Joyful according to Plato’s Timaeus and Empedocles? - Ferella, Chiara (Aestimatio)

(untitled) (Institute for Research in Classical Philosophy and Science, 2022)
Plato and Empedocles depict a universe that manifests beauty, goodness, reason, and bliss. This article aims to investigate why both philosophers felt it important to describe a cosmos that participates in a human emotion such as happiness. First, it will be shown how both Plato and Empedocles could not dispense with embodied human experience, including emotional experience, in the formation of cosmological concepts. Indeed, their respective cosmoi are constructed through notions derived from the conceptual domain of human agency. Second, attention will also be paid to Plato and Empedocles’ reconstruction of the notion of the happy life. The main argument advanced here is that both Plato and Empedocles conceive of their (macro)cosmos as a paradigm of behavior, so that the conception of a happy universe has a significant ethical function at the level of the microcosm, ultimately demonstrating the centrality of the concept of happiness in the doctrines of both authors.